Leipzigs Stellung im regionalen Funktionsgefüge - Lehmann, Edgar (ERDKUNDE, 1966)
After briefly sketching the location of Leipzig and the city's relations to its hinterland, the paper deals with economic and cultural functions of this area. It is shown that the agglomeration of industry and population in the Leipzig region, in particular the highly developed chemical industry, did not basically alter the regional structure. The reasons for this lie at least partly in the importance of Leipzig's central functions, which should not be underrated; these Leipzig was able to retain even under the impact of modern industrialisation. In this context the paper discusses the role of the fairs and emphasises their regional consequences in strengthening the forces tending to preserve the existing regional structure. The paper sketches also other branches of the economic life from an economic geographical aspect and points out the basic trends of their regional development.